1968
DOI: 10.3109/00365516809076978
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Measurement of the Calf Blood Flow by Strain-Gauge Plethysmography and the Calf Muscle Blood Flow Measured by133Xenon Clearance

Abstract: TONNESEN, K. H. Simultaneous Measurement of the Calf Blood Flow by Strain-Gauge Plethysmography and the Calf Muscle Blood Flow Measured by 133Xenon Clearance. Scand. J. elin. Lab. Invest. 21, 65-76, 1968.lS3Xenon clearance technique as a measure of the blood flow per unit weight of muscle tissue has been compared to venous occlusion plethysmography in the calf of normal subjects. The comparison was made during reactive hyperemia and in the post-exercise period. In the first mentioned experiments, no agreement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

1971
1971
1996
1996

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 10 publications
(5 reference statements)
0
4
0
Order By: Relevance
“…This may give problems such as spark formation in capacitors and insufficient RF power. The mean power dissipation (less than 4 mW/g muscle tissue) was far below the values recommended described in the literature (41), and we considered it harmless because of the high diffusion in skeletal muscle (42).…”
Section: Discussionmentioning
confidence: 80%
“…This may give problems such as spark formation in capacitors and insufficient RF power. The mean power dissipation (less than 4 mW/g muscle tissue) was far below the values recommended described in the literature (41), and we considered it harmless because of the high diffusion in skeletal muscle (42).…”
Section: Discussionmentioning
confidence: 80%
“…A mean difference of 0.14 ml/100ml/min was found between the two series of measurements, with a coefficient of repeatability of 0.17 ml/lOOm1!min. This was much less than the 20% inter-tester error found by Tonnesen (1968).…”
Section: Venous Occlusion Plethysmographymentioning
confidence: 67%
“…The variability in venous occlusion plethysmography is considered to be influenced by physiologic change, variation in technique and systematic error in calculating blood flow from the chart traces (Altenkirch et al 1990;Corbally and Brennan 1990;LeJemtel et al 1992;Tonnesen 1968) Values of 15-25% generally have been found for the coefficient of variation, with higher values in the arm and at rest. The reliability of the model used in our laboratory had previously been determined for both groups of patients using the method described by Bland and Altman (1986).…”
Section: Venous Occlusion Plethysmographymentioning
confidence: 99%
“…However, criticism has been levied against the '33Xe clearance technique [19, 203. The frequent deviation of the 'j3Xe clearance technique from the microsphere technique and the directly measured blood flow by drop counting has been thoroughly documented [ 19,211. However, as was done in the present study, this deviation can be minimized by using the fast monoexponential portion of the decay curve in calculation of blood flow [22,231 or by using the 'second slope method', as developed by Tonnesen and Sejrsen [l5], to allow time for injection trauma to subside. It is also apparent from the study by Bonde-Petersen et al [24] that the 'j3Xe clearance technique cannot be used in humans to measure very high blood flows.…”
Section: Discussionmentioning
confidence: 97%